Cops on campus: rethinking safety and confronting police violence - Suriel, Yalile (Abolition emancipation from the carceral, 2024)
Over the last five years, headlines have thrust campus police departments from relative obscurity into the national spotlight. Campus constituents have called for campus police, as a tangible manifestation of the War on Crime within the sphere of higher education, to be disarmed, defunded, and abolished. Using a multidisciplinary approach that draws from the fields of history, American studies, ethnic studies, criminology, higher education, and sociology, Cops on Campus provides critical perspectives on the organization and social consequences of campus policing. Chapters uncover details of the structure and culture of university police-some of the best-funded and largest private police forces in the nation-and examine the institution in relation to racialized and gendered violence, racial profiling, and the surveillance of marginalized communities on and off campus. The volume also features interviews with students, staff, and faculty activists to showcase efforts to redefine and reimagine campus safety and explore alternatives for the future